Prevalence and associated risk factors of prehypertension and hypertension among army personnel - Gurung, Sapana; Rai, Padma (Nepal Population Journal, 2018)
Hypertension (HTN) is most likely a common disease in the world. In every 3 adult ages over 20 years have this disease. As a consequence, Non-communicable diseases (NCDs), such as hypertension and other cardiovascular diseases are becoming increasingly important as causes of mortality and morbidity in all developing countries. The aim of this study is to determine the prevalence of pre-hypertension and hypertension among the Army personnel in Nepal. This was a cross-sectional descriptive study of 315 respondents, who met eligible criteria. All respondents were enumerated by census method using self-interviewing questionnaire focusing measurement of the blood pressure, weight and height along with the demographic and other socio-economic as well as cultural characteristics. The study shows that overwhelming respondents (77.5%) are normal. And about 13 percent respondents are seemed to be in the pre-hypertension, followed by stage I HTN (6%) and stage II HTN (3.5%). It also shows that there is a significant association between prevalence of hypertension and body mass index of the respondents.